2011
DOI: 10.1089/ten.tea.2010.0396
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Delivery of Dibutyryl Cyclic Adenosine Monophosphate to the Transected Spinal Cord Via Oligo [(Polyethylene Glycol) Fumarate] Hydrogels

Abstract: This study describes the use of oligo [(polyethylene glycol) fumarate] (OPF) hydrogel scaffolds as vehicles for sustained delivery of dibutyryl cyclic adenosine monophosphate (dbcAMP) to the transected spinal cord. dbcAMP was encapsulated in poly(lactic-co-glycolic acid) (PLGA) microspheres, which were embedded within the scaffolds architecture. Functionality of the released dbcAMP was assessed using neurite outgrowth assays in PC12 cells and by delivery to the transected spinal cord within OPF seven channel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 88 publications
(110 reference statements)
2
34
0
Order By: Relevance
“…OPF can be cross-linked by UV light and more importantly, its molecular weight controls the mechanical properties and degradation speed of the hydrogel. These properties make it broadly used in bone [58], osteochondral [59], musculotendinous [60], cardiovascular [61] and neural tissue engineering [62,63]. OPF could serve as spinal cord regeneration matrix mainly due to its compressive and flexural modulus which is similar to that of rat spinal cord [64].…”
Section: Polyethylene Glycol (Peg)mentioning
confidence: 99%
See 1 more Smart Citation
“…OPF can be cross-linked by UV light and more importantly, its molecular weight controls the mechanical properties and degradation speed of the hydrogel. These properties make it broadly used in bone [58], osteochondral [59], musculotendinous [60], cardiovascular [61] and neural tissue engineering [62,63]. OPF could serve as spinal cord regeneration matrix mainly due to its compressive and flexural modulus which is similar to that of rat spinal cord [64].…”
Section: Polyethylene Glycol (Peg)mentioning
confidence: 99%
“…Bone marrow derived MSCs were suspended in matrigel and seeded into scaffolds and transplanted into transected rat spinal cord injury model. The authors believed the sustained release of dbcAMP rescued axonal regeneration from MSCs induced inhibition and capillary formation, which in turn improved motor function [62].…”
Section: Polyethylene Glycol (Peg)mentioning
confidence: 99%
“…Acute PEG treatment after spinal cord trauma has also been reported to exert neuroprotective effects via the reduction of oxidative stress reactions . PEG is a widely used material for the design of biodegradable synthetic cross-linked hydrogels (Burdick et al, 2006;Cong et al, 2009;Gunn et al, 2005;Herten et al, 2009;Phelps et al, 2010;Qiao et al, 2005;Raeber et al, 2005;Rooney et al, 2011). PEG has several beneficial features, which are advantageous for soft tissue regeneration.…”
Section: Polyethylene Glycolmentioning
confidence: 99%
“…Previous studies in our laboratory have evaluated various polymers and cell types for nervous system repair. [32][33][34][35][36][37][38][39][40][41][42][43][44] Schwann cells loaded into polymer scaffold channels have demonstrated an increased capacity for supporting axonal regeneration when compared with other cell types such as neural stem cells or mesenchymal stem cells. 37,42 We have shown that biodegradable polymer hydrogel scaffolds seeded with Schwann cells are able to bridge the growth inhibitory lesion site and support axon regeneration in vivo.…”
mentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42][43][44] Schwann cells loaded into polymer scaffold channels have demonstrated an increased capacity for supporting axonal regeneration when compared with other cell types such as neural stem cells or mesenchymal stem cells. 37,42 We have shown that biodegradable polymer hydrogel scaffolds seeded with Schwann cells are able to bridge the growth inhibitory lesion site and support axon regeneration in vivo. 36,40 We have also compared the mechanical properties and regeneration supporting potential of various polymers, including poly(lactic-co-glycolic acid) (PLGA), poly(caprolactone fumarate) (PCLF), a neutral oligo[(polyethylene glycol) fumarate] (OPF) hydrogel, and a positively charged oligo [(polyethylene glycol) fumarate] (OPF+) hydrogel and determined that scaffolds fabricated from OPF+ support the most axon regeneration and have similar compression and flexural moduli to rat spinal cord.…”
mentioning
confidence: 99%